ANALYSIS OF STUDENTS' INTERESTS AND MOTIVATIONS IN PARTICIPATING PHYSICAL EDUCATION LEARNING - Febriansyah; Hendra, Jhony; Pilitan, Raja Bani; Saputra, Deka Ismi Mori; Wulandari, Titis (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
Physical education plays a vital role in developing students’ motor skills, physical abilities, and knowledge, while also fostering positive attitudes toward active lifestyles. Interest and motivation are essential factors influencing learning outcomes in physical education (PJOK) at the elementary school level. This study aims to analyze students’ interest and motivation in participating in PJOK learning. The research employed a quantitative descriptive design with purposive sampling. The sample consisted of 20 students from a population of 110, selected based on low initial motivation and interest in PJOK. Data were collected using a questionnaire and analyzed through percentage techniques. Results revealed that learning readiness (73%), personal interest (74%), teacher’s influence (71%), social support (78%), and ideals/aspirations (74%) were categorized as good. Meanwhile, the learning environment (65%), student ability (65%), physical condition (64%), and dynamic elements (67%) were categorized as sufficient. Overall, students’ interest and motivation in PJOK learning reached the “good” category, with an average of 70%. These findings highlight the importance of strengthening instructional strategies to enhance motivation and engagement. The study provides valuable insights for PJOK teachers to design more effective and supportive learning environments.